2021
DOI: 10.3390/jcm10122687
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Selection Procedures for Optimizing the Outcome of ICSI in Patients with NOA

Abstract: Retrieving spermatozoa from the testicles has been a great hope for patients with non-obstructive azoospermia (NOA), but relevant methods have not yet been developed to the level necessary to provide resolutions for all cases of NOA. Although performing testicular sperm extraction under microscopic magnification has increased sperm retrieval rates, in vitro selection and processing of quality sperm plays an essential role in the success of in vitro fertilization. Moreover, sperm cryopreservation is widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 264 publications
(313 reference statements)
0
11
0
Order By: Relevance
“…According to the World Health Organization laboratory manual for the examination and processing of human semen [ 23 ], HOST is advised in cases of asthenozoospermia to collect suitable spermatozoa for ICSI. Some studies suggested that HOST should be employed in a subsequent ICSI cycle following total fertilization failure [ 80 ].…”
Section: Advanced Methodsmentioning
confidence: 99%
“…According to the World Health Organization laboratory manual for the examination and processing of human semen [ 23 ], HOST is advised in cases of asthenozoospermia to collect suitable spermatozoa for ICSI. Some studies suggested that HOST should be employed in a subsequent ICSI cycle following total fertilization failure [ 80 ].…”
Section: Advanced Methodsmentioning
confidence: 99%
“…Like the HOS test, STFT and LAISS could give false positives for frozen sperm as the flagellum could spontaneously curl after freezing-thawing [ 53 54 ]. These two techniques, STFT and LAISS, have not been described in recent years, probably because their costs in terms of learning time (STFT) or in terms of equipment (LAISS) might limit their routine use in ART laboratories [ 53 54 57 ].…”
Section: Management Of Necrozoospermiamentioning
confidence: 99%
“…Therefore, there are several techniques to test the vitality of immobile spermatozoa. Most studies have focused on activating substances such as pentoxifylline (PTX) or theophylline describing their role in activating flagellar movement of immotile spermatozoa (for a review see [ 53 54 57 ]). PTX is a 3′ 5′ nucleotidase phosphodiesterase inhibitor that improves sperm motility by increasing intracellular cyclic adenosine monophosphate [ 58 ].…”
Section: Management Of Necrozoospermiamentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome of mTESE is greatly affected by the accuracy in testicular sperm processing techniques. Kaan Aydos and Oya Sena Aydos reviewed the available sperm selection procedures, as well as the different approaches to testicular sperm cryopreservation, providing valuable suggestions for embryologists and clinicians about how to effectively handle testicular specimens and testicular sperm to maximize the outcome of mTESE [ 11 ].…”
mentioning
confidence: 99%